Blood Pressure and Heart Rate Measurements Using Fiber Bragg Grating Sensor with Optical Power Detection Scheme - Wang, Yu-Jie; Wang, Likarn (Sensors (Basel, Switzerland), 2025)
A low-cost dual-FBG (fiber Bragg grating) architecture is employed to capture the pulse waveform of the artery at the subject’s wrist by measuring changes in optical power. The pulse transit time (PTT), pulse ascending time, and pulse descending time extracted from the pulse waveform are used in a blood pressure (BP) estimation model by fitting the measured BP with the reference BP obtained from a commercial sphygmomanometer. The estimation model is developed using data from 29 subjects at the age of 20 to 54. The results demonstrate that the errors between the calculated values and reference values of SBP and DBP for all of the 29 subjects both range from −4 to 5 mmHg with mean errors of 0.72 mmHg and 0.83 mmHg, respectively. The standard error can be found to be 2.45 and 2.59 mmHg for SBP and DBP, respectively. Also, it is found that this BP estimation model outperforms two BP models derived by considering PTT only.